Implementasi Reward dan Punishment dalam Menciptakan Lingkungan Kondusif Belajar Pada Mata Pelajaran Siroh di SDIT Al-Hikmah Depok - Rahmat Ramdhani; Siskha Putri Sayekti; Dul Rohman; M. Badran Fahma (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2023)
The purpose of this study was to determine the conducive learning environment for the Siroh subject in grades IV, V and VI at SDIT Al Hikmah Depok through the application of Reward and Punishment. This research is a qualitative research